SOCIAL ENTREPRENEURSHIP CHARACTER-BASED LEARNING DESIGN AT THE CENTER FOR COMMUNITY LEARNING ACTIVITIES - Sutarto, Joko; Raharjo, Tri Joko; Shofwan, Imam (PEOPLE: International Journal of Social Sciences, 2020)
Research objectives: (a) find the design of learning based on the planting of social entrepreneurship character in current The Center for Community Learning Activities (PKBM); and (b) formulate a proper conceptual design in the planting-based learning of social entrepreneurship characters in PKBM. Data collection is done through interviews, and observations. This research procedure follows the flow of literature studies, field foil, and design formulation. Research findings show: (a) The empirical design of learning based on the planting of social entrepreneurship characters conducted by administering life proficiency skills through regular theoretical learning activities conducted by all Tutors, and not involving business actors; and (b) while the design (conceptual) is suggested in the planting-based learning of social entrepreneurship character following the flow of theory and practice, technical assistance, giving life skills and internship programs with involving actors Efforts began to plan, implement, and evaluate, as well as mentoring business management aspects, marketing, and business funding.